Analisis Kritis Terhadap Fenomena Throning dalam Perspektif Agama Kristen (International Forum of Researchers and Lecturers, 2025)
The phenomenon of throning, which refers to the practice of seeking partners with high social status to enhance self-image, is increasingly prevalent among Generation Z. Although it may seem appealing, throning poses negative issues such as unrealistic expectations, a transactional view of relationships, and the potential for unhappiness that impacts individuals' mental health. This article aims to critically analyze throning behavior from the perspective of Christian Religious Education, emphasizing the importance of spiritual values in building healthy relationships. The research method employed is qualitative, using a literature review approach that involves analyzing written sources related to throning and Christian Religious Education. The findings indicate that throning contradicts the pursuit of a life partner, as well as the principles of love and respect for the intrinsic value of individuals taught in the Bible. The study concludes by affirming the need for a holistic approach to understanding relationships, grounded in spiritual values rather than social status. Recommendations for future research include more in-depth empirical studies on the impact of throning on mental health and interpersonal relationships, as well as a deeper exploration of Biblical knowledge, which highlights the importance of moral and spiritual values in relationship contexts, even in the digital age. It is hoped that individuals can build more authentic relationships through the lens of the Bible and glorify God.